Penggunaan Limbah Kopi Sebagai Bahan Penyusun Ransum Itik Peking dalam Bentuk Wafer Ransum Komplit - Muhammad Daud; Zahrul Fuadi; Sultana Sultana (Agricultural Faculty, 2013)
Effect of coffee waste as component of compiler ration peking duck in the form of wafer complete rationABSTRACT. Coffee waste is a by-product of coffee processing that potential to be used as feed stuff for peking duck. The weakness of this coffee waste, among others, is perishable, voluminous (bulky) and the availability was fluctuated so the processing technology is needed to make this vegetable waste to be durable, easy to stored and to be given to livestock. To solve this problem vegetable waste could be formed as wafer. This research was conducted to study effectiveness of coffee waste as component of compiler ration peking duck in the form of wafer complete ration This experiment was run in completely randomized design which consist of 4 feed treatment and 3 replications. Ration used was consisted of P0 = wafer complete ration 0% coffee waste (control), P1 = wafer complete ration 2,5% coffee waste, P2 = wafer complete ration 5% coffee waste, and P3 = Wafer complete ration 7,5% coffee waste. The Variables observed were: physical characteristic (aroma, color, and wafer density) and palatability of wafer complete ration. Data collected was analyzed with ANOVA and Duncan Range Test would be used if the result was significantly different. The result showed that the density of wafer complete ration coffee waste was significantly (P 0.05) differences between of treatment. Mean density wafer complete ration equal to: P0= 0,520,03, P1 =0,670,04, P2 =0,720,03, and P3 = 0,760.05 g/cm3. Wafer complete ration coffee waste palatability was significantly (P 0.05) differences between of treatment. It is concluded that of wafer complete ration composition 5 and 7,5% coffee waste was significantly wafer palatability and gave a highest wafer density. The ration P0 was the most palatable compare to other treatments for the experimental peking duck.